Averaging of Boundary-Value Problems with Parameters for Multifrequency Impulsive Systems - Lakusta, L. M.; Petryshyn, R. I.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
By using the averaging method, we prove the solvability of boundary-value problems with parameters for nonlinear oscillating systems with pulse influence at fixed times. We also obtain estimates for the deviation of solutions of the averaged problem from solutions of the original problem.